High performance thermosets with tailored properties derived from methacrylated eugenol and epoxy-based vinyl ester - Zhang, Yuehong; Li, Yuzhan; Kumar Thakur, Vijay; Gao, Zhenhua; Gu, Jiyou; Kessler, Michael R. (Wiley, 2018)
A renewable chemical, eugenol, is methacrylated to produce methacrylated eugenol (ME) employing the Steglich esterification reaction without any solvent. The resulting ME is used as a low viscosity comonomer to replace styrene in a commercial epoxy-based vinyl ester resin (VE). The volatility and viscosity of ME and styrene are compared. The effect of ME loadings and temperatures on viscosity of the VE-ME resin is investigated. Moreover, the thermo-mechanical properties, curing extent, and thermal stability of the fully cured VE-ME thermosets are systematically examined. The results indicate that ME is a monomer with low volatility and low viscosity, and therefore the incorporation of ME monomer in VE resins allows significant reduction of viscosity. Moreover, viscosity of the VE-ME resin can be tailored by adjusting ME loadings and processing temperature to meet commercial liquid molding technology requirements. The glass transition temperatures of VE-ME thermosets range from 139 to 199 °C. In addition, more than 95% of the monomer is incorporated and fixed in the crosslinked network structure of VE-ME thermosets. Overall, the developed ME monomer exhibits promising potential to replace styrene as an effective low viscosity comonomer. The VE-ME resins show great advantages for use in polymer matrices for high performance fiber-reinforced composites. This work showed great significance to the vinyl ester industry by providing detailed experimental support.
Keywords: Methacrylated eugenol (ME); Comonomer; Vinyl-ester (VE); Thermosets; Styrene replacement